The Legal Effect of Appointment and Possession of a Receiver Over the Property of a Company - Otu, Michael Takim; Nabiebu, Miebaka (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
A receiver in an action is an impartial person appointed by the court to collect and receive, pending the proceedings, the rents, issues, and profits of land or personal estate that it does not seem reasonable to the court that either party should collect or receive, or to enable the same to be distributed among the persons entitled. The appointment of a receiver does not in any way affect the right to the property over which he is appointed. The court takes possession of its receiver, and his possession is that of all parties to the action according to their titles. The receiver does not collect the rents and profits by virtue of any estate vested in him but by virtue of his position as an officer of the court appointed to collect property upon the title of the parties to the action. In the case of a fixed or floating charge, receivers and managers are appointed either by the court or by the debenture holders. In this article, we shall examine the legal effects of the appointment of a receiver by the court and out-of-court systems over the property of a company. This research is carried out using textual and contextual analysis.